From seed to seedling - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Vegetable seedling production manual FAO Plant Production and Protection Papers No 155. 1999. 84 pp. ISBN 925104385x US$ 22 E 25.80 FAO Sales and Marketing Group Viale delle Terme di Caracalla, 00100 Rome, Italy. Fax: +39 06 57 05 33 60 Email: